2013
DOI: 10.1055/s-0033-1340312
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Use of the Suzuki Coupling Reaction in the Synthesis of 4′-Alkyl-2′-hydroxyacetophenones

Abstract: International audienceA series of 4′-alkyl-2′-hydroxyacetophenones were prepared by Suzuki cross-coupling reactions of 4′-bromo-2′-hydroxyacetophenone. In these reactions, alkyl(trifluoro)borates were found to be better reactants than alkylboronic acids. 4′-Alkyl-2′-hydroxyacetophenones are key intermediates for the further synthesis of -lipoflavonoids that are more readily incorporated into lipid bilayer membranes than flavonoids and should, therefore, have superior -biological effects through increased bioav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…[20] The BF 3 K salts, used as substrates for cross-coupling reactions, were prepared in a straightforward manner from the corresponding boronic acids under non-etching conditions. It was found that Pd(OAc) 2 combined with RuPhos and NaOH facilitated coupling with sp 3 -hybridized reagents with minimal -hydride elimination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] The BF 3 K salts, used as substrates for cross-coupling reactions, were prepared in a straightforward manner from the corresponding boronic acids under non-etching conditions. It was found that Pd(OAc) 2 combined with RuPhos and NaOH facilitated coupling with sp 3 -hybridized reagents with minimal -hydride elimination.…”
Section: Resultsmentioning
confidence: 99%
“…General procedure III for sp 2 -sp 3 Suzuki Miyaura coupling (12a-12b, 13a-13b): [20] Bromo-(-)-trans-Δ 8 -tetrahydrocannabinol (6)/ (7) (1 equiv.) was dissolved in toluene (0.2M) and Pd(OAc) 2 (10 mol-%), RuPhos (20 mol-%), alkyl trifluoroborate salt (1.5 equiv.)…”
Section: General Informationmentioning
confidence: 99%
“…It was found that Pd(OAc)2 combined with RuPhos and NaOH facilitated coupling with sp 3 -hybridized reagents with minimal -hydride elimination. 20 The BF3K salts, used as substrates for crosscoupling reactions, were prepared in a straightforward manner from the corresponding boronic acids under non-etching conditions. 21 Elaborating on the essential difference of regioisomers 6 and 7, we converted 7 into naturally occurring  8 -THC (13a) and  8 -propyl-THC (13b) by successful Suzuki-Miyaura cross-coupling (Scheme 5).…”
Section: Methodsmentioning
confidence: 99%
“…The product was isolated by filtration and the flask and filter were rinsed with n-heptane (4 mL). The filtrated solid was dried under high vacuum and this afforded (20)…”
Section: -Propylbenzene-13-diol (1c)mentioning
confidence: 99%